Oyster Mushroom (Pleurotus ostreatus) Growth and Production On Straw and Brands Substrate Supplied with Nasa Liquid Organic Fertilizer (POC) - Marlin Tupa; Abdullah Sarijan; Nurhening Yuni Ekowati (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
This study aims to analyze the effect of adding NASA Liquid Organic Fertilizer (POC) supplements to the substrate on oyster mushroom (Pleurotus ostreatus) growth and production. The research design used in this study was a completely randomized design (CRD), with four levels of treatment with the addition of NASA POC. The treatment doses used were 0% NASA POC as control (A), 2.5% NASA POC (B), 3% NASA POC (C), and 3.5% NASA POC (D). Each treatment was repeated four times to obtain 16 treatment units. Each treatment unit consisted of 5 Baglogs, so the total sample observed was 80 Baglogs. Based on the parameters observed in this study, including the length of mycelium spread (LPM), the beginning of the emergence of pinheads (AMP), the number of pinheads (JP), the diameter of the oyster mushroom hood (DTJT), and the weight of the oyster mushroom (BBJT), the addition of NASA POC on the substrate. Growth has no significant effect on the growth and production of oyster mushrooms (Pleurotus ostreatus).